A physicochemical assessment of upper catchment within the Ayer Hitam Forest Reserve, Peninsular Malaysia - Siti Nurhidayu; Nordin, Siti Fatimah; Sulaiman, Mohd Sofiyan; Mohamad Kassim, Mohamad Roslan; Sang, Yan-Fang (Penerbit UMT, 2022)
Isolated forests located in rapidly developing areas play a crucial role in providing water resources, regulating climate, filtering water pollution, and mitigating flood events. The Ayer Hitam Forest Reserve (AHFR) is one of the most precious tracts of the remaining lowland dipterocarp forest in the highly urbanized state of Selangor, Malaysia. Until recently, there have been no comprehensive datasets available on hydrological data in AHFR. This study aims to assess the seasonal physicochemical characteristics from a matured secondary catchment forest in AHFR, which is surrounded by the metropolitan city of the Klang Valley. Its physical characteristics are denoted by streamflow, turbidity, and Total Suspended Solids (TSS). The chemical characteristics consist of dissolved oxygen (DO), temperature, pH, Electrical Conductivity (EC), salinity, and Total Dissolved Solids (TDS). The results indicated that the baseflow discharges ranged from 0.020 to 0.680 m3/s, while stormflow discharges ranged from 0.003 to 1.090 m3/s. Only pH and TSS are categorized under Class 3 during storm events. The findings implied that a catchment was capable of recharging the baseflow during low rainfall periods and producing high-quality water, which is important to safeguard the water resources and hydrological functions of a catchment within an isolated forest.